(untitled) (Jurnal Komunikasi Pembangunan, 2019)
Online media is utilized by Micro Small and Medium Enterprises (UMKM) in culinary field in Sub-district of Pancoran Mas, Depok City to market and promote the produuct so that can be recognized by public in order to assist the development of UMKM. The purpose of this research is to know how the relation between marketing communication through online media with business development. This research used quantitative approach through questionnaires supported by qualitative data through interview guides. The result of the the research showed that there is a relationship between marketing communication activity through online media viewed from variouus online media, message type, and message appeal with business development seen from amout of business outcome, the amount of labor and market coverage area. The majority of UMKM owners use a variety of online media and convey a diverse message type with the attractiveness of the message that interestingly made, so that the product can be know by many people and increased product orders resulting in increased sales, therefore making the owner of UMKM increase the labor.